A series of photosensitizers with incremental positive electric charges for photodynamic antitumor therapy. Issue 42 (8th August 2019) - Yan, Shufeng; Huang, Qingqing; Song, Xiaorong; Chen, Zhuo; Huang, Mingdong; Zhang, Juncheng
Abstract : In recent years, photodynamic therapy (PDT) studies have gained considerable attention as a non-invasive method used to fight cancer. Abstract : In recent years, photodynamic therapy (PDT) studies have gained considerable attention as a non-invasive method used to fight cancer. In this study, a series of structurally similar photosensitizers (PSs) with incremental positive electric charges (ZnPc-4, 8 and 12) was investigated via in vitro and in vivo experiments. Photodynamic antitumor studies of these PSs, including phototoxicities, cellular uptake, the production of reactive oxygen species (ROSs) and the process of apoptosis, were conducted in the murine breast carcinoma cell line 4T1. The results indicated that the amount of positive electric charges in PSs is a key factor in influencing the efficacy of PDT. Furthermore, we established a hepatocellular carcinoma (H22) tumor-bearing mouse model to detect the antitumor activities of three PSs. ZnPc-4, 8 and 12 demonstrated significant antitumor effects and no obvious systemic damages in vivo (PDT effects: ZnPc-4 > ZnPc-8 > ZnPc-12), suggesting that the amount of positive electric charges was important to PSs, as well as the PDT effects. Our study not only indicates that ZnPc-4, 8 and 12 were highly potent anticancer PSs, but also suggests that adjusting the amount of positive electric charges is able to promote the PDT effects in cancer therapy.